Direct regeneration and repair process of failed lithium nickel cobalt manganese oxide positive electrode material and application of direct regeneration and repair process

By using sodium hydroxide solution treatment and nickel cobalt manganese hydroxide precursor for high-temperature calcination in the nickel cobalt lithium manganese oxide positive electrode material, the safety hazards of high-temperature and high-pressure treatment in the existing technology are solved, and simple, safe and efficient are achieved The direct regeneration and repair of the product improves lithium replenishment efficiency and material stability.

CN119208797AActive Publication Date: 2024-12-27SHENZHEN RUISAIKE ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411352673.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

The prior art has the potential for hydrothermal treatment of nickel-cobalt-manganese oxide cathode material under high temperature and high pressure conditions, and it is not suitable for large-scale production, making it difficult to achieve simple, safe and efficient direct regeneration and repair.

Method used

The residual aluminum impurities were removed by sodium hydroxide solution. After decomposition treatment and high-temperature calcination, the nickel-cobalt-manganese hydroxide precursor was used for solid mixing and uniform addition, avoiding high-pressure sealing conditions, and lithium supplementation was completed through two high-temperature calcinations, achieving failure. Direct regeneration and repair of materials.

Benefits of technology

It significantly improves the lithium replenishment efficiency and the migration rate of lithium, improves the repair effect, avoids high-pressure safety hazards, and achieves low-cost, low-pollution and efficient material regeneration, and has simple operation and short process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208797A_ABST
    Figure CN119208797A_ABST
Patent Text Reader

Abstract

The invention discloses a direct regeneration and repair process and application of a failed lithium nickel cobalt manganate positive electrode material, and the direct regeneration and repair process comprises the steps of primary treatment, impurity removal pretreatment, mixing, high-temperature calcination and the like of the failed lithium nickel cobalt manganate positive electrode material. The direct regeneration and repair process of the failed lithium nickel cobalt manganate positive electrode material has the characteristics of simple operation, short flow, high safety and the like, and the directly regenerated and repaired lithium nickel cobalt manganate positive electrode material has excellent electrochemical performance and cycle performance, also has high stability, and can meet market requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of recycling and cyclic reuse of waste power lithium-ion batteries, and in particular to a direct regeneration and repair process for failed nickel-cobalt-manganese-oxide lithium positive electrode materials and applications thereof. Background Art

[0002] With the rapid development of electric vehicles and energy storage technology, the demand for nickel cobalt manganese oxide positive electrode materials has increased dramatically. The main components of nickel cobalt manganese oxide positive electrode materials (such as nickel, cobalt, manganese, etc.) are scarce resources. In order to meet people's daily application needs while improving resource utilization efficiency, it is necessary to repair and reuse failed nickel cobalt manganese oxide positive electrode materials. How to repair failed nickel cobalt manganese oxide positive electrode materials has become a hot topic for scientists.

[0003] The prior art has a treatment method for regenerating and repairing completely failed nickel cobalt manganese oxide positive electrode materials, one of which is to subject the completely failed nickel cobalt manganese oxide positive electrode materials to degradation treatment, followed by annealing treatment to obtain pretreated nickel cobalt manganese oxide positive electrode materials, and then disperse the pretreated nickel cobalt manganese oxide positive electrode materials in a LiOH solution for hydrothermal reaction, and obtain reprocessed nickel cobalt manganese oxide positive electrode materials after the reaction is completed, and finally the nickel cobalt manganese oxide positive electrode materials obtained by the hydrothermal reaction are mixed with a small amount of LiOH and calcined at high temperature twice to obtain repaired and regenerated nickel cobalt manganese oxide positive electrode materials. However, the hydrothermal treatment adopted by the above method is carried out under high temperature and high pressure conditions, and there are safety issues in the lithium replenishment process. It is not applicable to industrial large-scale (hundreds of kilograms) production and is prone to safety hazards.

[0004] Therefore, it is necessary to design a simple, safe and efficient process for directly regenerating and repairing failed nickel cobalt manganese oxide positive electrode materials to solve the above problems. Summary of the invention

[0005] In view of the defects in the prior art, the present invention proposes a direct regeneration and repair process for failed nickel-cobalt-manganese-oxide lithium positive electrode materials and its application.

[0006] The present invention provides a direct regeneration and repair process for failed nickel-cobalt-manganese-oxide lithium positive electrode materials, comprising the following steps:

[0007] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a sodium hydroxide solution to remove residual aluminum impurities in the spent positive electrode material, and obtaining a preliminarily treated spent nickel cobalt manganese oxide material after stirring, filtering and drying;

[0008] S2: performing impurity removal treatment on the initially treated spent nickel cobalt manganese oxide material obtained in step S1 at 250-500° C. to obtain a pretreated spent nickel cobalt manganese oxide material. This step can remove impurities such as the diaphragm and PVDF in the material;

[0009] S3: The pretreated spent nickel cobalt manganese oxide material obtained in step S2 is mixed with lithium salt and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:(0.1-0.6) to obtain a mixed material; the mass ratios of the spent nickel cobalt manganese oxide material and lithium salt and nickel cobalt manganese hydroxide are 1:0.2:0.1, 1:0.2:0.2, 1:0.2:0.3, 1:0.2:0.4, 1:0.2:0.5 and 1:0.2:0.6.

[0010] S4: The mixed material obtained in step S3 is heated to 450-650°C in an air atmosphere for the first heat preservation, and then heated to 800-1000°C for the second heat preservation. After the heat preservation is completed, the temperature is lowered to room temperature to obtain a directly regenerated nickel cobalt manganese oxide lithium material.

[0011] The present invention uses a nickel-cobalt-manganese hydroxide precursor for the first time to directly repair failed positive electrode materials. The lithium salt and the precursor are uniformly added to the failed nickel-cobalt-manganese oxide lithium by solid mixing, and then the lithium replenishment process is completed after two high-temperature calcinations. This avoids lithium replenishment in a high-pressure closed container, improves the lithium replenishment efficiency and the migration rate of lithium, and greatly improves the repair effect. The rock salt phase in the failed material can be transformed into a layered structure to achieve recovery of the failed structure.

[0012] Furthermore, the step S1 also includes sieving the initially treated spent lithium nickel cobalt manganese oxide material, wherein the sieving can separate coarse and fine materials to obtain a powder with uniform particle size; the mesh size used for the sieving is 50-300 mesh, such as 50, 100, 150, 200, 250 or 300 mesh.

[0013] Furthermore, the time for the impurity removal treatment in step S2 is 1-5 hours.

[0014] Furthermore, the lithium salt is selected from one or more of lithium hydroxide, lithium carbonate, lithium nitrate and lithium chloride.

[0015] Furthermore, the step S3 also includes doping Nb2O5 with a mass fraction of 0-1%wt. Doping Nb2O5 can further stabilize the layered structure and improve the long-term cycle stability of the regenerated positive electrode material.

[0016] Furthermore, in step S4, the first insulation time is 1-3 hours, and the second insulation time is 1-5 hours. High-temperature calcination in an air atmosphere can further improve the stability of the repair material.

[0017] Furthermore, the concentration of the sodium hydroxide solution in step S1 is 0.5-3 mol / L.

[0018] Furthermore, the mass ratio of the spent nickel cobalt manganese oxide material pretreated in step S3 to the lithium salt and nickel cobalt manganese hydroxide is 1:0.2:0.2.

[0019] The present invention also provides the application of the direct regeneration and repair process in treating waste power lithium-ion batteries.

[0020] The present invention also provides a nickel-cobalt-manganese-oxide lithium positive electrode material repaired by the direct regeneration repair process.

[0021] In summary, compared with the prior art, the present invention achieves the following technical effects:

[0022] (1) The direct regeneration and repair process of the failed nickel-cobalt-manganese-oxide lithium positive electrode material provided by the present invention completes lithium replenishment by high-temperature calcination after mixing, avoids the use of closed high-pressure conditions, and significantly improves the safety of the repair process;

[0023] (2) The direct regeneration and repair process of the failed nickel-cobalt-manganese-oxide lithium positive electrode material provided by the present invention can directly regenerate the positive electrode material at a low cost;

[0024] (3) The direct regeneration and repair process of the failed nickel-cobalt-manganese-oxide lithium positive electrode material provided by the present invention can significantly improve the repair efficiency;

[0025] (4) The direct regeneration and repair process of the failed nickel-cobalt-manganese-oxide lithium positive electrode material provided by the present invention can be calcined in an air atmosphere to achieve the repair and improvement of the electrochemical performance of the material;

[0026] (5) The direct regeneration and repair process of the failed nickel-cobalt-manganese-oxide positive electrode material provided by the present invention is simple to operate and has a short process;

[0027] (6) The direct regeneration and repair process for failed nickel-cobalt-manganese-oxide lithium positive electrode materials provided by the present invention does not use materials that may pollute the environment during the repair process, thereby reducing CO2 emissions. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 This is a charge and discharge curve diagram of the failed nickel cobalt manganese oxide positive electrode material (NCM523) used in Example 1 of the present invention;

[0030] Figure 2The charge and discharge curve of the directly regenerated nickel cobalt manganese oxide lithium positive electrode material (NCM523) obtained in Example 1 of the present invention;

[0031] Figure 3 The charge and discharge curve diagram of the commercial nickel cobalt lithium manganese oxide positive electrode material (NCM523) used in the present invention;

[0032] Figure 4 This is a charge and discharge curve diagram of the directly regenerated nickel cobalt manganese oxide positive electrode material (NCM523) obtained in Example 4 of the present invention;

[0033] Figure 5 This is a charge and discharge curve diagram of the directly regenerated nickel cobalt manganese oxide positive electrode material (NCM523) obtained in Example 5 of the present invention;

[0034] Figure 6 The charge and discharge curve of the directly regenerated nickel cobalt manganese oxide lithium positive electrode material (NCM523) obtained in Comparative Example 1 of the present invention;

[0035] Figure 7 This is a charge and discharge curve diagram of the directly regenerated nickel cobalt manganese oxide lithium positive electrode material (NCM523) obtained in Comparative Example 2 of the present invention;

[0036] Figure 8 It is a rate performance comparison diagram of the failed nickel cobalt manganese oxide positive electrode material (SNCM523-BM), the directly regenerated nickel cobalt manganese oxide positive electrode material (RNCM523) of Example 1 of the present invention, the commercial nickel cobalt manganese oxide positive electrode material (CNCM523), and the directly regenerated nickel cobalt manganese oxide positive electrode material (rNCM523) of Comparative Example 1 of the present invention;

[0037] Fig. 9 It is a comparison chart of the long-term cycle performance of the failed nickel cobalt manganese oxide positive electrode material (SNCM523-BM), the directly regenerated nickel cobalt manganese oxide positive electrode material (RNCM523) of Example 1 of the present invention, the commercial nickel cobalt manganese oxide positive electrode material (CNCM523), and the directly regenerated nickel cobalt manganese oxide positive electrode material (rNCM523) of Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0039] Example

[0040] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.

[0041] 1. The sources of raw materials for the embodiments and comparative examples are as follows:

[0042] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present invention are commercially available, wherein the failed nickel cobalt manganese oxide positive electrode material (failed NCM523) was purchased from a battery disassembly manufacturer.

[0043] 2. Various performance test methods

[0044] The regenerated and repaired nickel cobalt manganese oxide positive electrode material was prepared into positive electrode slurry with a mass ratio of positive electrode material: conductive agent SP: binder PVDF: NMP = 80:10:10:100, coated on aluminum foil, and cut into electrode sheets after vacuum drying at 100°C for 12 hours. Subsequently, CR2032 button batteries were assembled in a glove box according to the button battery assembly process.

[0045] (1) Gram capacity performance test: tested by Xinwei battery testing system, the charging cut-off voltage is 4.3V, and the minimum discharge cut-off voltage is 2.5V.

[0046] (2) Long cycle stability test: The test is conducted using the Xinwei battery testing system with a rate set to 0.5C.

[0047] (3) Rate performance test: The test was conducted at rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 4C, with each rate being cycled five times.

[0048] Example 1

[0049] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a 1 mol / L sodium hydroxide solution, stirring and filtering, drying at 100° C., and sieving the material with a 300-mesh sieve to obtain a preliminarily treated spent nickel cobalt manganese oxide material;

[0050] S2: performing a de-impurity treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 300° C. for 2 hours to obtain a pre-treated spent nickel cobalt manganese oxide material;

[0051] S3: mixing the pretreated spent lithium nickel cobalt manganese oxide material obtained in step S2 with lithium hydroxide and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:0.2, and then adding 0.5%wt Nb2O5 and grinding with a mortar to obtain a mixed material;

[0052] S4: heating the mixed material obtained in step S3 to 500° C. at a rate of 5° C. / min in an air atmosphere, keeping the temperature for 2 hours for the first time, then raising the temperature to 850° C. at a rate of 3° C. / min, keeping the temperature for 3 hours, and cooling the temperature to room temperature after the end of the keeping temperature to obtain a directly regenerated nickel cobalt manganese oxide lithium material;

[0053] Figure 1 This is the charge and discharge curve of the failed nickel cobalt manganese oxide positive electrode material (NCM523) used in Example 1. It can be seen that the capacity of the failed nickel cobalt manganese oxide is less than 20 mAh / g, indicating that the crystal structure of the failed nickel cobalt manganese oxide is severely damaged;

[0054] Figure 2 The charge and discharge curve of the repaired and regenerated nickel cobalt manganese oxide lithium positive electrode material (NCM523) obtained in Example 1 shows that the specific capacity of the material at 0.5C reaches more than 149 mAh / g;

[0055] Figure 3 The charge and discharge curves of commercial nickel cobalt manganese oxide lithium positive electrode material (NCM523) show that the regenerated positive electrode material of the present invention is comparable to the commercial positive electrode material in terms of capacity;

[0056] Figure 8 It is shown that the directly regenerated nickel cobalt manganese oxide positive electrode material (RNCM523) of Example 1 of the present invention has a capacity of 158.66 mAh / g under 0.1C charge and discharge conditions, which is comparable to the commercial nickel cobalt manganese oxide positive electrode material (CNCM523). Fig. 9 It demonstrated its excellent cycling performance and was able to maintain a capacity retention rate of 81.06% after 250 cycles.

[0057] Example 2

[0058] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a 3 mol / L sodium hydroxide solution, stirring and filtering, drying at 100° C., and sieving the material with a 100-mesh sieve to obtain a preliminarily treated spent nickel cobalt manganese oxide material;

[0059] S2: performing a de-impurity treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 500° C. for 1 hour to obtain a pre-treated spent nickel cobalt manganese oxide material;

[0060] S3: mixing the pretreated spent lithium nickel cobalt manganese oxide material obtained in step S2 with lithium hydroxide and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:0.2, and then adding 0.1%wt Nb2O5 and grinding with a mortar to obtain a mixed material;

[0061] S4: The mixed material obtained in step S3 is heated to 450°C at a rate of 5°C / min in an air atmosphere, and kept warm for 3 hours for the first time, and then the temperature is raised to 1000°C at a rate of 3°C / min, and kept warm for 1 hour. After the insulation is completed, the temperature is cooled to room temperature to obtain a directly regenerated nickel cobalt manganese oxide lithium material.

[0062] Example 3

[0063] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a 0.5 mol / L sodium hydroxide solution, stirring and filtering, drying at 100° C., and sieving the material with a 50-mesh sieve to obtain a preliminarily treated spent nickel cobalt manganese oxide material;

[0064] S2: performing a de-impurity treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 250° C. for 5 hours to obtain a pre-treated spent nickel cobalt manganese oxide material;

[0065] S3: mixing the pretreated spent lithium nickel cobalt manganese oxide material obtained in step S2 with lithium nitrate and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:0.2, and then adding 1%wt Nb2O5 and grinding with a mortar to obtain a mixed material;

[0066] S4: The mixed material obtained in step S3 is heated to 650°C at a rate of 5°C / min in an air atmosphere, and kept warm for 1 hour for the first time, and then the temperature is raised to 900°C at a rate of 3°C / min, and kept warm for 2 hours. After the insulation is completed, the temperature is cooled to room temperature to obtain a directly regenerated nickel cobalt manganese oxide lithium material.

[0067] Example 4

[0068] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a 1 mol / L sodium hydroxide solution, stirring and filtering, drying at 100° C., and sieving the material with a 300-mesh sieve to obtain a preliminarily treated spent nickel cobalt manganese oxide material;

[0069] S2: performing a de-impurity treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 300° C. for 2 hours to obtain a pre-treated spent nickel cobalt manganese oxide material;

[0070] S3: mixing the pretreated spent lithium nickel cobalt manganese oxide material obtained in step S2 with lithium hydroxide and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:0.1, and then adding 0.5%wt Nb2O5 and grinding with a mortar to obtain a mixed material;

[0071] S4: The mixed material obtained in step S3 is heated to 500°C at a rate of 5°C / min in an air atmosphere, and kept warm for 2 hours for the first time, and then the temperature is raised to 850°C at a rate of 3°C / min, and kept warm for 3 hours. After the insulation is completed, the temperature is cooled to room temperature to obtain a repaired nickel cobalt manganese oxide lithium material.

[0072] Example 5

[0073] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a 1 mol / L sodium hydroxide solution, stirring and filtering, drying at 100° C., and sieving the material with a 300-mesh sieve to obtain a preliminarily treated spent nickel cobalt manganese oxide material;

[0074] S2: performing a de-impurity treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 300° C. for 2 hours to obtain a pre-treated spent nickel cobalt manganese oxide material;

[0075] S3: mixing the pretreated spent lithium nickel cobalt manganese oxide material obtained in step S2 with lithium hydroxide and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:0.6, and then adding 0.5%wt Nb2O5 and grinding with a mortar to obtain a mixed material;

[0076] S4: The mixed material obtained in step S3 is heated to 500°C at a rate of 5°C / min in an air atmosphere, and kept warm for 2 hours for the first time, and then the temperature is raised to 850°C at a rate of 3°C / min, and kept warm for 3 hours. After the insulation is completed, the temperature is cooled to room temperature to obtain a repaired nickel cobalt manganese oxide lithium material.

[0077] Comparative Example 1

[0078] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a 1 mol / L sodium hydroxide solution, stirring and filtering, drying at 100° C., and sieving the material with a 300-mesh sieve to obtain a preliminarily treated spent nickel cobalt manganese oxide material;

[0079] S2: performing a de-impurity treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 300° C. for 2 hours to obtain a pre-treated spent nickel cobalt manganese oxide material;

[0080] S3: mixing the pretreated spent lithium nickel cobalt manganese oxide material obtained in step S2 with lithium hydroxide and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:0, and then adding 0.5%wt Nb2O5 and grinding with a mortar to obtain a mixed material;

[0081] S4: The mixed material obtained in step S3 is heated to 500°C at a rate of 5°C / min in an air atmosphere, and kept warm for 2 hours for the first time, and then the temperature is raised to 850°C at a rate of 3°C / min, and kept warm for 3 hours. After the insulation is completed, the temperature is cooled to room temperature to obtain a repaired nickel cobalt manganese oxide lithium material.

[0082] Comparative Example 2

[0083] S1: placing the spent nickel cobalt manganese oxide positive electrode material in a 1 mol / L sodium hydroxide solution, stirring and filtering, drying at 100° C., and sieving the material with a 300-mesh sieve to obtain a preliminarily treated spent nickel cobalt manganese oxide material;

[0084] S2: performing a de-impurity treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 300° C. for 2 hours to obtain a pre-treated spent nickel cobalt manganese oxide material;

[0085] S3: mixing the pretreated spent lithium nickel cobalt manganese oxide material obtained in step S2 with lithium hydroxide and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:0.7, and then adding 0.5%wt Nb2O5 and grinding with a mortar to obtain a mixed material;

[0086] S4: The mixed material obtained in step S3 is heated to 500°C at a rate of 5°C / min in an air atmosphere, and kept warm for 2 hours for the first time, and then the temperature is raised to 850°C at a rate of 3°C / min, and kept warm for 3 hours. After the insulation is completed, the temperature is cooled to room temperature to obtain a repaired nickel cobalt manganese oxide lithium material.

[0087] The electrochemical performance of the regenerated and repaired nickel cobalt manganese oxide positive electrode materials provided in Examples 1-5 and Comparative Examples 1-2 was tested, and then compared with the test results of the commercial nickel cobalt manganese oxide positive electrode material NCM523. The results are shown in Table 1:

[0088] Table 1. Performance test results of examples and comparative examples

[0089]

[0090] By comparing Example 1, Examples 4-5 with Comparative Examples 1-2, it can be seen that the amount of precursor nickel cobalt manganese hydroxide added will affect the regeneration effect. As the amount of precursor increases, the capacity will increase, but when the added amount exceeds a certain proportion, the capacity will decrease to a certain extent. Increasing the proportion of precursor can improve the lithium replenishment efficiency and the lithium migration rate, but adding too little or too much will inhibit this process, making the repair effect worse.

[0091] The test data in Table 1 about the battery capacity under 0.5C charge and discharge conditions and the capacity retention rate after 250 cycles under 0.5C charge and discharge conditions show that the direct regeneration and repair process in Examples 1-5 of the present invention is used, by pre-treating the failed nickel cobalt manganese oxide positive electrode material, adding a special precursor and a lithium salt thereto, and then calcining it in two steps under an air atmosphere to obtain the regenerated and repaired nickel cobalt manganese oxide positive electrode material, the electrochemical performance is significantly improved, can meet the standards for commercial applications, and has obvious advantages over the comparative example.

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A direct regeneration and repair process for failed nickel-cobalt-manganese-oxide lithium positive electrode material, characterized in that: The steps include: S1: placing the spent nickel cobalt manganese oxide positive electrode material in a sodium hydroxide solution, stirring, filtering and drying, thereby obtaining a preliminarily treated spent nickel cobalt manganese oxide material; S2: performing impurity removal treatment on the preliminarily treated spent nickel cobalt manganese oxide material obtained in step S1 at 250-500° C. to obtain a pretreated spent nickel cobalt manganese oxide material; S3: mixing the pretreated spent nickel cobalt manganese lithium oxide material obtained in step S2 with lithium salt and nickel cobalt manganese hydroxide in a mass ratio of 1:0.2:(0.1-0.6) to obtain a mixed material; S4: The mixed material obtained in step S3 is heated to 450-650°C in an air atmosphere for the first heat preservation, and then heated to 800-1000°C for the second heat preservation. After the heat preservation is completed, the temperature is lowered to room temperature to obtain a directly regenerated nickel cobalt manganese oxide lithium material.

2. The direct regeneration repair process according to claim 1, characterized in that: The step S1 also includes sieving the initially treated spent lithium nickel cobalt manganese oxide material, and the mesh size used for the sieving is 50-300 meshes.

3. The direct regeneration repair process according to claim 1, characterized in that: The time for the impurity removal treatment in step S2 is 1-5 hours.

4. The direct regeneration repair process according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium hydroxide, lithium carbonate, lithium nitrate and lithium chloride.

5. The direct regeneration repair process according to claim 1, characterized in that: The step S3 also includes doping Nb2O5 with a mass fraction of 0-1%wt.

6. The direct regeneration repair process according to claim 1, characterized in that: In step S4, the first insulation time is 1-3 hours, and the second insulation time is 1-5 hours.

7. The direct regeneration repair process according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step S1 is 0.5-3 mol / L.

8. The direct regeneration repair process according to claim 1, characterized in that: The mass ratio of the spent nickel cobalt manganese oxide material pretreated in step S3 to the lithium salt and nickel cobalt manganese hydroxide is 1:0.2:0.

2.

9. Application of the direct regeneration and repair process according to any one of claims 1 to 8 in treating waste power lithium-ion batteries.

10. The lithium nickel cobalt manganese oxide positive electrode material repaired by the direct regeneration repair process according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for regenerating positive electrode active material in LiNi1 / 3Co1 / 3Mn1 / 3O2 waste lithium ion battery

    CN104466295A

  • Method for circularly preparing spherical lithium nickel cobalt manganese oxide by lithium-ion battery positive plate

    CN105375078A

  • Recycling method of nickel cobalt lithium manganate battery, regenerated nickel cobalt lithium manganate material and application

    CN113113690A

  • Preparation method of lithium transition metal oxide

    CN1493522A